Barriers in implementing green construction in Malaysia / Nurul Syazwani Mohammad Nazon - Mohammad Nazon, Nurul Syazwani (Faculty of Architecture, Planning and Surveying, 2015)
The increasing of the world population has led to the increasing more demand for the construction of such as houses, buildings, and public facilities, therefore, it will lead to an increase in construction activity. Nowadays the construction industry is one of the largest sectors that are responsible for high-energy consumption, solid waste generation, global greenhouse depletion. If these resources are misused, the ability of the future generations to adequately meet their needs will be significantly reduced. In order to overcome the increasing concern, Green Construction is being adopted. In Malaysia, especially government took drastic actions in promoting and emphazing Green Construction. The objectives of the studies are determining the issues preventing, success elements in implementing green construction in Malaysia mostly in Klang Valley. These studies also are the measure taken and supported by the government in promoting, encourage and emphasizing Green Construction project were determine too. Data was collected by sending questionnaire to obtain their response on these issues. Based on the study, Green Construction is widely understood by majority industry players in construction, the implementation is not being widely carried out. There are several barriers in implementing green construction compare to the overall project carried out.